2014
DOI: 10.1155/2014/298473
|View full text |Cite
|
Sign up to set email alerts
|

Biomedical Relation Extraction: From Binary to Complex

Abstract: Biomedical relation extraction aims to uncover high-quality relations from life science literature with high accuracy and efficiency. Early biomedical relation extraction tasks focused on capturing binary relations, such as protein-protein interactions, which are crucial for virtually every process in a living cell. Information about these interactions provides the foundations for new therapeutic approaches. In recent years, more interests have been shifted to the extraction of complex relations such as biomol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
49
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
1
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 77 publications
(50 citation statements)
references
References 58 publications
0
49
0
1
Order By: Relevance
“…Progress has been made in automating biological event extraction from biomedical texts [1], but little attention has been given to identifying and associating the biological context in which such events occur. Biological context, however, often plays a critical role in interpreting these events.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Progress has been made in automating biological event extraction from biomedical texts [1], but little attention has been given to identifying and associating the biological context in which such events occur. Biological context, however, often plays a critical role in interpreting these events.…”
Section: Introductionmentioning
confidence: 99%
“…We make the following contributions in this paper: (1) provide an analysis of the context-event inter-sentential relation extraction problem, (2) develop a corpus of contextevent relations for evaluation, and (3) present first results of an inter-sentential context extraction and association model that provides a baseline for future work.…”
Section: Introductionmentioning
confidence: 99%
“…IntAct [8]). The types of biological relations in text can be a) semantic, b) grammatical, c) negation and coreference [15]. This work focuses on identifying semantic relations among biological entities.…”
Section: Introductionmentioning
confidence: 99%
“…Text mining approaches vary from simple co-occurrence [12] -where two entities are considered to be related if they occur in the same abstract, to those using sophisticated Natural Language processing (NLP) [13] and machine learning [14] techniques. Excellent reviews of relation extraction methods can be found in [11], [15], [16].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation